LEADERSHIP DEVELOPMENT AS LIVED PRACTICE: AN AUTOETHNOGRAPHIC STUDY OF FOUNDING AND LEADING VOLUNTEER-BASED HIGH SCHOOL CLUB - Khachatur Babayan (PEOPLE: International Journal of Social Sciences, 2026)
This autoethnographic study, grounded in theories of identity formation and experiential learning, examines how founding and leading a volunteer-oriented school club shaped my leadership development. Drawing on my experience as founder of an Astronomy Club, I analyze one year of weekly reflective journal entries documenting the challenges and insights of coordinating peer learning and community engagement. Using an inductive approach that combined manual thematic analysis with AI-assisted pattern recognition via QualiGPT, I conducted a human-AI co-analytic process to surface patterns across the journal entries. In this study, QualiGPT functioned solely as a methodological support tool (not the object of analysis), helping to enhance the visibility of recurring ideas while all interpretation remained grounded in the journal data. The findings reveal that leadership evolves not through authority but through empathy, shared responsibility and reflective practice. Volunteering and club participation create spaces where personal passion aligns with community service, shaping leadership through reflective practice, shared responsibility and sustained participation. This study contributes to emerging discussions on reflective pedagogy and the use of AI in qualitative research, demonstrating how self-initiated service experiences cultivate grounded, collaborative and digitally literate student leaders.